Activity of sulfated polysaccharides from microalgae Porphyridium cruentum over degenerative mechanisms of the skin (2012)
ABSTRACT: Marine microalgae are an innovative source of bioactive compounds which have achieved great relevance in medical, pharmaceutical and cosmetic fields. Using bubble column photobioreactors we have obtained a constant and controlled culture of the red microalga Porphyridium cruentum, known for its high production of sulfated polysaccharides (SPs), which have demonstrated activity on several biological mechanisms. In this paper we have evaluated the inhibitory effect of these compounds on three enzymes which are involved in the degradation of key substrates for the good appearance of skin. The results of the present study indicated that the SPs of P. cruentum do not display inhibitory activity on bacterial collagenase neither significant antioxidant activity. However, a high inhibition of hyaluronidase equivalent to an average of 96.6 ± 0.3% was obtained when the SPs were applied in a concentration ranging from 0.25 to 2.5 mg/mL. In addition, an inhibition of 46.0 ± 7.1 % was caused on enzymatic activity of elastase at a concentration of 5 mg/mL. These in vitro studies suggest that the SPs of marine microalga Porphyridium cruentum can be used as active ingredients in cosmetic and pharmaceutical formulations in order to maintain good health and appropriate skin appearance.